Substitution of Chemical Fertilizer with Organic MOL Fertilizer to Increase Crop Productivity - Lestari, Bibit Lilik (Indonesian Journal of Agriculture and Environmental Analytics, 2024)
Agriculture in Indonesia faces major challenges in terms of sustainability and productivity, especially with the high dependence on chemical fertilizers that can damage the soil in the long run. This study aims to determine the impact of chemical fertilizer substitution with MOL organic fertilizer on rice productivity in Village X, East Java. This research used a quantitative approach with a comparative case study. Data were collected during one rice growing season from two treatment groups using different fertilizers. Primary data were obtained through field observation, direct measurement, and sample analysis, while secondary data were collected from village reports and previous studies. Data analysis was conducted using descriptive statistics and Structural Equation Modeling (SEM). The results showed that chemical fertilizer increased rice productivity higher in the short term than MOL organic fertilizer. Independent T-test results showed significant differences, with chemical fertilizers producing significantly higher yields (t-value 12.45, p-value 2.306). However, the use of chemical fertilizers negatively impacts soil quality and the environment in the long run. In contrast, MOL organic fertilizer improved soil quality despite lower yields. SEM analysis showed that the substitution of chemical fertilizer with MOL organic fertilizer had a significant effect but with a smaller estimated coefficient compared to the use of chemical fertilizer. MOL organic fertilizer provides long-term benefits by improving soil fertility so that to achieve high production and protect the environment, a combination of using chemical fertilizers at optimal doses and gradually using organic fertilizers is highly recommended to support sustainable agriculture.